2012
DOI: 10.4269/ajtmh.2012.11-0446
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Human Hookworm Infections in Economically Disadvantaged Communities in Peninsular Malaysia

Abstract: Abstract. Species identification of human hookworm infections among eight communities in rural areas of Peninsular Malaysia was determined during 2009-2011. Fecal samples were examined by microscopy and subsequently, the internal transcribed spacer 2 and 28S ribosomal RNA region of Necator americanus and Ancylostoma spp. were sequenced. Overall, 9.1% (58 of 634) were identified positive by microscopy for hookworm infection, and 47 (81.0%) of 58 were successfully amplified and sequenced. Sequence comparison fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 29 publications
4
36
0
Order By: Relevance
“…Prevalence of other intestinal parasites detected in these humans were as reported in our previous study [26]. As for domestic carnivores, Toxocara canis infection (33/105, 31.4%) was the highest, followed by Trichuris vulpis (21/105, 19.7%), Entamoeba spp.…”
Section: Resultssupporting
confidence: 84%
“…Prevalence of other intestinal parasites detected in these humans were as reported in our previous study [26]. As for domestic carnivores, Toxocara canis infection (33/105, 31.4%) was the highest, followed by Trichuris vulpis (21/105, 19.7%), Entamoeba spp.…”
Section: Resultssupporting
confidence: 84%
“…The results obtained were compared to iodine stained direct smear and conventional semi-nested PCR as reported previously [2], [34]. The study protocol (MEC Ref.…”
Section: Methodsmentioning
confidence: 99%
“…These findings confirmed the previous epidemiological survey indicating that individuals who had close contact with dogs were more likely to be infected with A. ceylanicum. [33][34][35] Although the notion of zoonotic transmission of A. lumbricoides and T. trichiura between humans and dogs is still largely unclear, these animals may act as significant mechanical transmitter of ascariasis in the human population especially in communities where the habit of indiscriminate defecation exist. Molecular-based tool studies have shown that dogs act as disseminators and environmental contaminators of A. lumbricoides in communities where indiscriminate defecation is common.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Moreover, more studies are reporting on the zoonotic ancylostomiasis caused by A. ceylanicum in humans in endemic areas in Southeast Asia. 23,[34][35][36] A recent genetic study to provide further evidence on zoonotic transmission of A. ceylanicum between humans and animals in Malaysia showed that some of the A. ceylanicum strains from both the human and animal host in the same geographical location are clustered together within the same group. 37 This provides evidence that dogs and humans share genetically similar genotypes of A. ceylanicum within the same geographical location.…”
Section: Discussionmentioning
confidence: 99%